Measuring labour productivity through labour requirement approach: the Malaysian experience - Abdul Rashid, Zakariah; Chan, Khai Yew (Universiti Putra Malaysia Press, 1997)
The present paper measures labour productivity by estimating direct and indirect labour requirements per unit of output. Labour requirements are estimated by using an input-output technique. The paper uses two input-output tables for two different periods to ensure the results are more consistent. The results of the study were then tested by comparing them with the ordinary measures of labour productivity such as value added per labour; salaries and wages per labour and output per labour. It is interesting to note that although for the whole economy direct labour requirement appears to be the consistent measure of labour productivity, for some sectors of the economy indirect labour requirement is also important.